Damage Characteristics of Coated Cylindrical Shells Subjected to Underwater Contact Explosion - Zhi-fan Zhang; Fu-ren Ming; A-man Zhang (Shock and Vibration)
It is of great significance for the protective design of submarine to study the influences of coverings on the damage characteristics of single and double cylindrical shells subjected to underwater contact explosions. The SPH models of single and double cylindrical shells coated with foam silicone rubber are established to analyze shockwave propagation, damage characteristics, and elastoplastic responses, which provides reasonable parameters of covering position and thickness. The results can be concluded as follows: the superposition of multiple waves may cause the inhomogeneity and discontinuity; for the single cylindrical shell with inner or outer coverings, the damage mode is mainly tensile and shear failure is caused by detonation waves and detonation products; compared with out-covering approach, the in-covering approach has better antishock performance; the best protective effect comes out when the thickness of covering is close to that of the shell; as for the double cylindrical shell without interlayer water, the destruction of inner shell mainly results from the puncture of high-speed fragments from the outer shell, so for the outer shell, out-covering is a better choice; however, since the interlayer water is very effective in protecting the inner shell, in-covering will be better for the inner shell.